2020
DOI: 10.1016/j.psychres.2020.112977
|View full text |Cite
|
Sign up to set email alerts
|

Impact Of Sars-Cov-2 And Its Reverberation In Global Higher Education And Mental Health

Abstract: Background: According to UNESCO's monitoring, more than 160 countries implemented nationwide closures, which impacted over 87% of the world's student population. Several other countries implemented localized school closures; should these closures become nationwide, millions of additional learners will experience education disruption. Universities from around the world have been uncertain about how long the coronavirus crisis will last and how it might affect the mental health of students and faculty. The psych… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
192
0
45

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 345 publications
(305 citation statements)
references
References 0 publications
5
192
0
45
Order By: Relevance
“…Negative physiological impact of stress will come out. 16 Therefore, improving cognition and knowledge is conductive to enhance the ability of stress response. We found that the majority of pregnant women worried to know whether their children could be born healthily and smoothly.…”
Section: Popularized Knowledge About Covid-19mentioning
confidence: 99%
“…Negative physiological impact of stress will come out. 16 Therefore, improving cognition and knowledge is conductive to enhance the ability of stress response. We found that the majority of pregnant women worried to know whether their children could be born healthily and smoothly.…”
Section: Popularized Knowledge About Covid-19mentioning
confidence: 99%
“…Studies suggest that students in face to face courses could have higher academic success as they feel they learn better from direct instruction and instructor presence [ 6 , 24 , 39 , 40 , 49 , 64 ]. Based on such assumptions, moving to ERT is raising questions related to its efficacy and the impact it can have on all stakeholders in higher education in terms of health, political, economic, social and psychological elements [ 2 , 69 , 81 ]. However, skeptics of ERT who believe it is less than face to face may fail to realize that ERT uses several practices and features of face to face teaching, but does so using alternative methods [ 8 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…The United Nations Educational, Scientific and Cultural Organization (UNESCO) estimates that 60% of all students globally are affected by school closures [ 4 ], and numerous experts anticipate an adverse impact on mental health due to the pandemic and its containment measures [ 5 , 6 , 7 , 8 , 9 ]. Mental health problems and disorders are a serious public health issue in students with a fifth of students affected worldwide [ 10 , 11 ]. General population studies find current prevalence rates of 1.5% to 3.0%, lifetime rates of 4.0–7.0% [ 12 , 13 , 14 ], and substantial burden and impairment [ 15 ].…”
Section: Introductionmentioning
confidence: 99%